2011
DOI: 10.1590/s0102-79722011000200016
|View full text |Cite
|
Sign up to set email alerts
|

Socio-emotional well-being and academic achievement: evidence from a multilevel approach

Abstract: Even though social and emotional well-being has been proposed as a main goal of education, its association with academic achievement is usually overlooked, particularly considering that educational institutions are requested to show academic outcomes, and thus their focus is on cognitive development and academic training. This study adopts a multilevel perspective to test this association among Chilean elementary students, considering features at individual (socio-emotional well-being, self esteem, and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
29

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 38 publications
(31 reference statements)
5
44
1
29
Order By: Relevance
“…However, research in the last decade has reported inconsistent relationships between various aspects of wellbeing and academic achievement (e.g. Heckman, Stixrud & Urzua, 2006;Berger, Alcalay, Torretti & Milicic, 2011;Suldo & Shaffer, 2008;Saab & Klinger, 2010;Nicholson, Lucas, Berthelsen & Wake, 2012). Heckman et al (2006), for example, used data from the 1979 National Longitudinal Survey of Youth (participants aged 14 to 22 years-old) to demonstrate that non-cognitive traits, in this case self esteem (Rosenberg, 1965) and locus of control (Rotter, 1966), can be a more powerful predictor of school and life success than cognitive traits such as IQ.…”
Section: Wellbeing and Educational Achievementmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research in the last decade has reported inconsistent relationships between various aspects of wellbeing and academic achievement (e.g. Heckman, Stixrud & Urzua, 2006;Berger, Alcalay, Torretti & Milicic, 2011;Suldo & Shaffer, 2008;Saab & Klinger, 2010;Nicholson, Lucas, Berthelsen & Wake, 2012). Heckman et al (2006), for example, used data from the 1979 National Longitudinal Survey of Youth (participants aged 14 to 22 years-old) to demonstrate that non-cognitive traits, in this case self esteem (Rosenberg, 1965) and locus of control (Rotter, 1966), can be a more powerful predictor of school and life success than cognitive traits such as IQ.…”
Section: Wellbeing and Educational Achievementmentioning
confidence: 99%
“…Similarly, a cross-sectional survey of 674 Chilean students aged nine to 11 years-old found that self esteem predicted academic achievement (grade average). It was also reported that wellbeing measured by a 52 item Chilean wellbeing scale (Arab, 2009), social integration, classroom social climate and peer social networks were not predictors of academic achievement (Berger, et al, 2011). In a sample of 349 ten to 16 year olds Suldo and Shaffer (2008) measured wellbeing using the Students' Life Satisfaction Scale (Huebner, 1991) and the Positive and Negative Affect Scale for Children (Laurent et al, 1999).…”
Section: Wellbeing and Educational Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Videogames that transmit positive content such as "Mario," may be associated with higher achievement [67] because they could improve a person's sense of well-being [65,66], which has been shown to increase achievement [75]. Seligman [66] believes that gaming can promote people's emotions and quality of relationships in a positive direction.…”
Section: A Theoretical Background For the Effect Of Videogames On Achmentioning
confidence: 99%
“…After examining the correlations between key study variables and testing the assumptions of the analysis, I tested my hypotheses using a three-step hierarchical linear regression [75]. In the first step, I tested to see whether videogame use predicted academic achievement.…”
Section: Analytic Approachmentioning
confidence: 99%